A technique for measuring the frictional torque of articular cartilage and replacement biomaterials. (September 2020) - Mahmood, Humaira; Shepherd, Duncan E.T.; Espino, Daniel M.
Highlights: This study develops a technique for the measurement of the frictional torque of articular cartilage and potential replacement biomaterials. On load application from 10 to 100 N, the mean torque magnitude range is of 0.08 to 0.11 N m, 0.08 to 0.09 N m as well as 0.07 to 0.09 N m, for articular cartilage, calcium alginate alone and in combination with articular cartilage, respectively. A statistically significant relationship exists between torque magnitude and load ( p < 0.05), for all specimen variations assessed. Abstract: Understanding the tribological behaviour of articular cartilage enables the development of effective replacement biomaterials. This study presents a technique for the investigation of the frictional torque of articular cartilage, for the assessment of replacement biomaterials. A calcium alginate hydrogel was used as the biomaterial for this study. Three different specimen types were examined to include articular cartilage, calcium alginate hydrogel, alone, and in combination with articular cartilage. An axial load, varying from 10 to 100 N, was applied to the specimen and the frictional torque measured whilst an indenter underwent axial rotation from 0° to 2° to 0° for 100 cycles. The resulting frictional torque magnitude was evaluated with a smooth curve fitting function. Linear regression identified a statistically significant relationship between torque magnitude and axial load ( p < 0.05) for all specimen variations. From 10 to 100 N of applied load, mean torque magnitude ranged from 0.08±0.010 to 0.11±0.013 N m, 0.08±0.012 to 0.09±0.016 N m and 0.07±0.017 to 0.09±0.020 N m (mean ± standard deviation), for articular cartilage, calcium alginate separately and in combination with articular cartilage, respectively. This study has established a suitable frictional torque testing protocol for potential cartilage replacement biomaterials.